Pengembangan Aplikasi Optimasi Rute Destinasi Wisata di Banyuwangi Menggunakan Modern Android Development (MAD) Pattern (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2022)
The closest route optimization problem is a classic problem that is still often found in everyday life, one of them is the Traveling Salesman Problem (TSP). This study aims to find solutions in the form of optimal distances to various tourist destinations in Banyuwangi. In this study, the author uses the Python programming language as the backend and the Kotlin programming language as the frontend of the Android application as part of Modern Android Development. The results of the system evaluation, namely Black Box and User Acceptance Test on the application, show that the system that has been carried out can be concluded that the functional system can work well without experiencing bugs or problems on every available feature and page. In designing the application, the author uses the Modern Android Development pattern.